Analysis of a failed pipe elbow in geothermal production facility. (October 2017) - Kusmono,; Khasani,
Highlights: A leakage at the elbow used in the geothermal production facility was found after 2 months in service. The main cause of failure was investigated through conducting standard failure analysis methods. Results indicated that the cause of failure was erosion-corrosion by the presence of wall thinning. Abstract: Failure of a pipe elbow used in geothermal production facility was reported to occur after 2 months in service. A leak was found to form at the bottom of elbow of horizontal pipe. The main cause of failure was investigated through conducting standard failure analysis including visual examination, chemical analysis, mechanical characterization, metallurgical examinations using optical microscopy in combination with scanning electron microscopy (SEM) equipped with energy dispersive X-ray (EDX) analysis and corrosion test using a three-electrode potential technique. Results of this investigation indicated that the failure of elbow was caused by an erosion-corrosion with the presence of wall thinning in leak area. The failure mechanism was discussed in this paper.